Incidence and variability in receipt of phenotype-desirable antimicrobial therapy for Enterobacterales bloodstream infections among hospitalized United States patients - Rena C. Moon; Shawn H. MacVane; Joy David; Jacob B. Morton; Ning Rosenthal; Kimberly C. Claeys (Cambridge University Press, 2024)
Abstract Background: Using a large, geographically diverse, hospital-based database in the United States (Premier PINC AI Healthcare Database), we aimed to describe the proportion and characteristics of patients receiving phenotype-desirable antimicrobial therapy (PDAT) among those hospitalized with Enterobacterales bloodstream infections. Methods: Adult patients with an admission between January 1, 2017 and June 30, 2022 with ≥1 blood culture positive for Escherichia coli, Klebsiella oxytoca, Klebsiella pneumoniae, or Proteus mirabilis and receiving an empiric antibiotic therapy on blood culture collection (BCC) Days 0 or 1 were included. Receiving PDAT (defined as receipt of any antimicrobial categorized as "desirable" for the respective phenotype) on BCC Days 0−2 was defined as receiving early PDAT. Results: Among 35,880 eligible patients, the proportion of patients receiving PDAT increased (from 6.8% to 22.8%) from BCC Day 0−4. Patients who received PDAT (8,193, 22.8%) were more likely to visit large (500 + beds, 36% vs 31%), teaching (45% vs 39%), and urban (85% vs 82%) hospitals in the Northeast (22% vs 13%) compared to patients not receiving PDAT (all P <. 01). Among patients receiving PDAT, 61.4% (n = 5,033) received it early; they had a lower mean comorbidity score (3.2 vs 3.6), were less likely to have severe or extreme severity of illness (71% vs 79%), and were less likely to have a pathogen susceptible to narrow-spectrum β-lactams (31% vs 71%) compared to patients in the delayed PDAT group (all P < .01). Conclusions: The proportion of patients receiving desirable therapy increased between BCC Day 0 and 4. Receipts of PDAT and early PDAT were associated with hospital, clinical, and pathogen characteristics.